The Effect of Motivation and Work Discipline on Job Satisfaction with Compensation as an Intervening Variable at the Representative Office of Bank Indonesia Pematangsiantar - Fandi Wardana Sinuraya; Isa Indrawan (International Journal of Management, Economic and Accounting, 2024)
This study aims to see the Influence of Motivation and Work Discipline on Job Satisfaction with Compensation as an Intervening Variable at the Bank Indonesia Pematangsiantar Representative Office. Human resources are the most important factor in the growth and development of an organization or business. That in the conditions of globalization, the quality of human beings in companies is always a competitive material. Companies that want to grow and develop well must organize their human resources intellectually, spiritually, creatively, morally and responsibly. The results of this study are as follows: Work Discipline has a positive and significant effect on Job Satisfaction with an original sample value of 0.267 and a p value of 0.048. Work Discipline had a psoitative and significant effect on Compensation with the original sample value of 0.269 and p values of 0.042. Compensation had a psoitative and significant effect on job satisfaction with the original sample value of 0.350 and p values of 0.011. Motivation had a positive and significant effect on Job Satisfaction with the original sample value of 0.315 and p values of 0.045. Motivation had a positive and significant effect on Compensation with the original sample value of 0.624 and p values of 0.000. Work Discipline had a positive and significant effect on Job Satisfaction through Compensation with the original sample value of 0.094 and p values of 0.105. Motivation had a positive and significant effect on Job Satisfaction through Compensation with the original sample value of 0.218 and p values of 0.014.